Film funding, policy and reception: a study of two ‘independent’ film productions / Ismail Norazman - Norazman, Ismail (2018)
This study will highlight the issues and problems of the feature film fund in Malaysia through two case studies on local film production, Nasi Lemak 2.0 and KIL. Focus will be given to the financing process of both film productions and related funds, governmental policies and critical reception, all of which will be examined through the political economy approach. This study will also examine in detail how the process of creativity and production planning activities involving the budget, starting from the procurement sources of funds until the final product is completed. This case study will use qualitative as its research paradigm, with methods being interviews, exploratory, descriptive and discourse analysis. In ensuring the extent to which both films have gained success in various aspects, this study also traces their critical receptions by critics and specialist audiences. In line with the development agenda of a more progressive film industry in Malaysia, the main goal of this study is to unravel the problem of film funding among low and middle budget filmmakers in Malaysia, especially the younger generation who possesses high creativity and great potential to co-develop the local film industry. Independent productions in Malaysia can be produced to meet the demand of both commercial and critical successes as demonstrated by Nasi Lemak 2.0 and KIL, despite having to face issues of raising funds and certain policy constraints. In this case, it is desirable that younger generation of filmmakers be encouraged by the government to continue to actively produce high quality films. This is because the development of the film industry in Malaysia is seen as vital to preserving the local creative and cultural industry through the injection of balanced and sustainable fund in propelling both the human capital and economy forward.